2016
DOI: 10.47210/bjohns.2016.v24i3.89
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in South Sharqiya in Oman and its Impact in ENT Patients- A Retrospective Study

Abstract: Introduction Vitamin D deficiency has multitude of causes and can present with varying clinical manifestations. Studies show that it can lead on to recurrent respiratory infections, ear infections and deafness. Vitamin D also has immunomodulant action. Here we discuss the varying features concerning an Otolaryngologist in general as far as Vitamin D metabolism is concerned. Materials and Methods This retrospective study was performed on 800 patients 152 males and 648 females of different soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…We found that 79.4% of our study population had serum vitamin D levels below 30 ng/mL. Similarly, a study conducted in Oman found that 79% of the study population had vitamin D levels below 30 ng/mL and the study population had normal serum calcium and alkaline phosphatase levels (26). Furthermore, 80.3% of the study population were found to have levels <30 ng/mL in a study conducted in northern France, and 25(OH)D levels were found to correlate positively with 1,25(OH) 2 D and negatively with parathyroid hormone, but did not correlate with serum calcium or phosphate levels (27).…”
Section: Discussionsupporting
confidence: 75%
“…We found that 79.4% of our study population had serum vitamin D levels below 30 ng/mL. Similarly, a study conducted in Oman found that 79% of the study population had vitamin D levels below 30 ng/mL and the study population had normal serum calcium and alkaline phosphatase levels (26). Furthermore, 80.3% of the study population were found to have levels <30 ng/mL in a study conducted in northern France, and 25(OH)D levels were found to correlate positively with 1,25(OH) 2 D and negatively with parathyroid hormone, but did not correlate with serum calcium or phosphate levels (27).…”
Section: Discussionsupporting
confidence: 75%